Women and its contribution in education era of 4.0 reviewed from Islamic perspective - Eka Danik Prahastiwi; Sugiyono Sugiyono (Institut Studi Islam Muhammadiyah Pacitan, 2022)
This study conducted with the purpose to know women contribution in education in 4.0 era from perspective Islam. This study is literature review oriented to script, book, document, and newspaper which are related with digital literacy and education. Result of this study show that there are opportunity and challenges the role of women in revolution era 4.0. reviewed from. The opportunity is women can used internet as source of education for their child, while the challenge is negative content on internet. Reviewed from Islamic perception, women has important role as first madrasa for their children, so women must be wise in selecting internet content appropriate for children. It would be better if the use of internet is done by using it for positive and religious things